Effect of Collector Tilt Angle on the Performance of a Residential Solar-Heating-and-Cooling System - Arsalis, Alexandros; Alexandrou, Andreas (Journal of Advanced Thermal Science Research, 2015)
A residential solar-heating-and-cooling (SHC) system is a possible alternative for the reduction of fossil fuel consumption to cover residential energy loads. These systems can cover all thermal loads, i.e. space heating, space cooling and domestic hot water preparation. Space cooling is fulfilled through a heat-activated (hot water), single-effect LiBr-water absorption chiller. Proper operation of such a system requires coupling of the solar collector array to a hot water storage tank with auxiliary heating. Auxiliary heating, in this case in the form of a diesel-fired boiler, is necessary to supplement heating in the storage tank when demand exceeds solar heating availability. In this study emphasis is given on the effect of the collector tilt angle (slope) on the performance of a SHC system. A constant slope throughout the year simplifies system configuration and maintenance, but on the other hand a variable slope improves performance, in terms of energy efficiency, and thereby lowers the operating cost of auxiliary heating. The results of the study show that it is economically beneficial to vary the slope throughout the year (on a monthly basis), since 233/year can be saved when a variable slope is used.